Journal of Biomimetics, Biomaterials and Biomedical Engineering. Vol. 51. (Journal of Biomimetics, Biomaterials and Biomedical Engineering Ser., 2021)
The 51st volume of "Journal of Biomimetics, Biomaterials and Biomedical Engineering" contains papers that reflect the latest results of scientific research and engineering decisions in the fields of biomaterials for implantology and prosthesis, biomechanics approach for human motion rehabilitation; the processing of medical images, and medical signals for the goals of various diagnostic purposes; application of information technologies in the biomedical practice. We hope that this volume will be helpful for many researchers and engineers from the different branches of biomedical engineering. Bioactive Glass, Calcium Phosphate, Titanium, Biocompatibility, Antibacterial Property, Femur Implant, Dental Implant, Mechanical Properties, Medical Image Processing, Lower Limbs Exoskeleton, Image Segmentation, Electrocardiogram, Discrete Wavelet Transform, Human-Computer Interaction, Gesture Recognition Materials Science, General Engineering, Bioscience and Medicine.